A Neoinstitutionalist Proposal to Study the BRICS - Guerrero, Mario Guillermo (2022)
This article seeks to contribute to the current disciplinary discussion about the BRICS from a neoinstitutionalist perspective. Here, we understand BRICS as an international institution which has deepened its technical-bureaucratic dynamics after the trust effect that was created from coordination and consistency experiences around aspects of the international economic agenda during the 2008/2009 economic-financial crisis. Therefore, our analytical proposal approaches the BRICS from its three institutional elements: its deliberation spaces; its information system; and its institutional incentive system. In summary, we consider that the proposed approach will allow us to understand in greater detail what institutional factors and features affect the probability of reaching consensus and cooperation among the BRICS member countries, as well as to identify in greater detail the institutional particularities that differentiate the BRICS from similar institutional experiences.